Rotary ultrasonic machining of hard-to-machine materials - Churi, Nikhil (Kansas State University, 2010)
Titanium alloy is one of the most important materials used in major segments of industries such as aerospace, automobile, sporting goods, medical and chemical. Market survey has stated that the titanium shipment in the USA has increased significantly in last two decades, indicating its increased usage. Industries are always under tremendous pressure to meet the ever-increasing demand to lower cost and improve quality of the products manufactured from titanium alloy. Similar to titanium alloys, silicon carbide and dental ceramics are two important materials used in many applications. Rotary ultrasonic machining (RUM) is a non-traditional machining process that combines the material removal mechanisms of diamond grinding and ultrasonic machining. It comprises of a tool mounted on a rotary spindle attached to a piezo-electric transducer to produce the rotary and ultrasonic motion. No study has been reported on RUM of titanium alloy, silicon carbide and dental ceramics. The goal of this research was to provide new knowledge of machining these hard-to-machine materials with RUM for further improvements in the machining cost and surface quality. A thorough research has been conducted based on the feasibility study, effects of tool variables, effects of machining variables and wheel wear mechanisms while RUM of titanium alloy. The effects of machining variables (such as spindle speed, feed rate, ultrasonic vibration power) and tool variables (grit size, diamond grain concentration, bond type) have been studied on the output variables (such as cutting force, material removal rate, surface roughness, chipping size) and the wheel wear mechanisms for titanium alloy. Feasibility of machining silicon carbide and dental ceramics is also conducted along with a designed experimental study.
Keywords: rotary ultrasonic machining; titanium; silicon carbide; dental ceramics; wheel wear mechanisms; force model; Engineering, Aerospace (0538); Engineering, Automotive (0540); Engineering, Industrial (0546); Engineering, Mechanical (0548)